Optimizing management strategies to enhance wheat productivity in the North China Plain under climate change - Baohua Liu; Ganqiong Li; Yongen Zhang; Ling Zhang; Dianjun Lu; Peng Yan; Shanchao Yue; Gerrit Hoogenboom; Qingfeng Meng; Xinping Chen (Journal of Integrative Agriculture, 2025)
Accurately estimating the wheat yield potential under climate changes is essential for assessing food production capacity. However, studies based on crop modeling and imperfect management experiment data frequently underestimate the wheat yield potential. In this study, we evaluated wheat yield potential based on the CERES-Wheat model and a well-managed 10-year (2008–2017) field study in the North China Plain (NCP), and further identified the critical climate and management yield-limiting factors for improving wheat yield potential and closing the wheat yield gap. Our results revealed that wheat yield potential averaged 10.8 t ha–1 in the recent decade. The low growing degree days (GDD) in the pre-winter growing season (592°C d) and solar radiation in the whole growth season (3,036 MJ m–2) are the most critical climatic factors limiting wheat yield potential in the current production system. Nonetheless, wheat yield potential in the NCP is projected to decline during 2040–2059 by 1.8 and 5.1% under the representative concentration pathway (RCP) 4.5 and RCP8.5 scenarios, respectively, without considering the elevated CO2 concentration. However, the positive influence of CO2 fertilization will be sufficient to offset these negative impacts from climatic warming and solar dimming, ultimately leading to an enhancement in wheat yield potential during 2040–2059 by 7.5 and 9.8% compared to the baseline under RCP4.5 and RCP8.5, respectively. To improve the wheat yield potential, we recommend selecting an appropriate planting date (5 October) and planting density (400 plants m–2) that align with light and temperature conditions during the wheat growing season. In addition, optimizing the timing and rate of water application (three times, 270 mm) and fertilizer use (based on in-season root zone nitrogen management) is crucial for closing the wheat yield gap. This study underscores the importance of adopting multiple management practices that account for complex climate–crop–soil interconnections to enhance the wheat yield based on a long-term field experiment under the changing climate.